Research on the Prediction Model of Blasting Vibration Velocity in the Dahuangshan Mine - Jiang Guo; Chen Zhang; Shoudong Xie; Yi Liu (Applied Sciences, 2022)
In order to improve the prediction accuracy of blast vibration velocity, the model for predicting the peak particle velocity of blast vibration using the XGBoost (Extreme Gradient Boosting) method is improved, and the EWT–XGBoost model is established to predict the peak particle velocity of blast vibration by combining it with the EWT (Empirical Wavelet Transform) method. Calculate the relative error and root mean square error between the predicted value and measured value of each test sample, and compare the prediction performance of the EWT–XGBoost model with the original model. There is a large elevation difference between each vibration measurement location of high and steep slopes, but high and steep slopes are extremely dangerous, which is not conducive to the layout of blasting vibration monitoring equipment. The vibration velocity prediction model adopts the numerical simulation method, selects the center position of the small platform as the measurement point of the peak particle velocity, and studies the variation law of the blasting vibration velocity of the high and steep slopes under the action of top blasting. The research results show that the EWT–XGBoost model has a higher accuracy than the original model in the prediction of blasting vibration velocity; the simultaneous detonation method on adjacent high and steep slopes cannot meet the relevant requirements of safety regulations, and the delayed detonation method can effectively reduce the blasting vibration of high and steep slopes. The shock absorption effect of the elevation difference within 45 m is obvious.